Review of The Profession: A Memoir of Community, Race, and the Arc of Policing in America - Gillette, Shanon (International Journal of Police Science, 2022)
Book: The Profession: A Memoir of Community, Race, and the Arc of Policing in America, by Bill Bratton and Peter Knobler (New York: Penguin Press, 2021), 512 pages, ISBN-10 0525558195 (hardcover), ISBN-13 978-0525558194 (hardcover).